Maintenance Management Practices For Hostel Facility: A Case Study (Journal of Engineering and Health Sciences, 2019)
The practices of conventional methods for maintenance management in Kolej Universiti Islam Melaka (KUIM) faced many issues due to poor service delivery, inadequate finance, and poor maintenance plan and maintenance backlogs. The purpose of this study is to improve the conventional method practices which tend to be ineffective in KUIM. The selected KUIM is based on conventional method practices and its major problems, attempt to implement computerised technology and the willingness of staff to share their experiences. The responses from semi-structured interview with engineer and assistant engineer were recorded using video camera and transcribed verbatim. The overall findings of this research indicated; poor service delivery, inadequate financial, poor maintenance planning and maintenance backlogs. There is also need to overcome less man power competencies of maintenance management practices which existed KUIM. In addition, the study also found that the KUIM still use conventional maintenance management processes in managing hostel facility condition. The proposed solutions are intended to be used for maintenance management practices at KUIM in order to provide high-quality of hostel facility with safe and healthy environments.